Back plate electroplating for high aspect ratio processes. Issue 2 (2nd May 2017) - Marasso, Simone Luigi; Benetto, Simone; Para, Isabella; Ottone, Chiara; Mombello, Domenico; Perrone, Denis; Ferrero, Sergio; Scaltrito, Luciano; Pugliese, Diego; Cocuzza, Matteo; Pirri, Fabrizio Candido
Abstract : Purpose: In this process the electrical contact is brought to the backside of a standard silicon wafer. The details of the entire process are disclosed, from the photolithography processes to the electrodepositing step, and a model for electrical contact was designed. Design/methodology/approach: The localized Cu growth of high aspect ratio (AR) microstructures was obtained through an SU-8 photolithography by exploiting the optimal adhesion on the silicon surface and the possibility of generating thick layers with a single spun process Findings: The experimental results showed an unexpected behaviour that is theoretically explained in detail considering the energy band theory. The obtained geometries showed a remarkable 6:1 AR without any adhesion problem. The non-invasive front-side manipulation represents a noteworthy improvement and simplification for the design of a multi-step production process. Originality/value: An alternative technological approach, called back plate electroplating, has been carried out to obtain Cu growth on the front side of a standard n-type Si wafer through a back side electrical contact. This technique was then applied to fabricate a master for hot-embossing in a LIGA (Lithographie, Galvanoformung, Abformung)-like process flow. For this purpose, an SU-8 thick mask on a standard n-doped wafer was used. Finally, by using this process, it was possible to obtain high AR Cu geometries, avoiding any complex designing and patterning of the contacts on the front side and thus ensuring good adhesion of the SU-8.